Hubungan Problematic Smartphone Use dengan Revenge Bedtime Procrastination pada Pelajar Tingkat MTs/SMP di Kecamatan X - Qonita Rohima; Zulian Fikry (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
This study aims to determine the level of problematic smartphone use (PSU) and revenge sleep procrastination (RBP) among MTs/SMP students in District X, while also examining the relationship between the two variables. The problem of excessive smartphone use among adolescents is increasingly important to study because it can impact sleep quality, learning concentration, and mental health. This research approach uses a quantitative correlational method with data collection through a bold questionnaire (Google Form). The research sample consisted of 103 MTs/SMP students in District X who were selected using an incidental sampling technique. The RBP variable measurement scale was developed by the researcher with reference to aspects proposed by Kroese et al. (2014). Meanwhile, the PSU Scale was developed based on dimensions formulated by Foerster et al. (2015), including withdrawal, desire, loss of control, dependence on peers, and negative life consequences. The results of the correlation analysis showed that PSU had a very strong positive relationship with RBP (r = 0.833) and was statistically significant (p < 0.000). This means that the higher a person's tendency to experience problematic smartphone use, the greater the likelihood of revenge bedtime delay. Among the dimensions of PSU, withdrawal showed the highest correlation with RBP (r = 0.831). This was followed by negative life consequences (r = 0.778), craving (r = 0.577), loss of control (r = 0.489), and dependence on peers (r = 0.333). Overall, this study concludes that PSU plays a significant role in increasing RBP trends among students. These findings highlight the urgent need for awareness and intervention programs to reduce excessive smartphone use among adolescents. Therefore, the results of this study are expected to serve as a reference for schools and parents in designing strategies to prevent the negative impacts of smartphone use on adolescents.